Pemberdayaan Masyarakat melalui Pelatihan Keselamatan dan Kesiapsiagaan Kebencanaan Berbasis Kemaritiman di Wilayah Aceh Tamiang Pasca Bencana Banjir Bandang - Masringgit Marwiyah Nst; Nurmaliana Sari Siregar; Meriah Kita Deliana N; Muhammad Sahid; Yusnidah Yusnidah; Restu Mujiono; Dirhamsyah Dirhamsyah; Yefta Vianus Marbun; Nursyahrul Ritonga; Nurul Hafilda (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2026)
Aceh Tamiang is a coastal region highly vulnerable to hydrometeorological disasters, including flash floods that have repeatedly affected settlements along riverbanks and coastal areas. Following the flash-flood disaster, the community required strengthened capacity in disaster safety and preparedness, particularly maritime-based approaches, given that most residents work as fishermen and live along the coast and riverbanks. This community empowerment program aimed to improve the community's knowledge, attitudes, and skills in facing disasters through maritime safety and disaster preparedness training. The methods included socialization, theoretical training, evacuation simulation, and practice with safety equipment (life jackets, rubber boats, and evacuation signage), which were evaluated through pre-tests, post-tests, and participatory observation. The results showed an increase in participants' knowledge and skills in identifying hazard signs, evacuation routes, and maritime-based self-rescue procedures. The community also demonstrated a more prepared and responsive attitude toward potential subsequent disasters. In conclusion, participatory maritime-based training effectively empowered the coastal community of Aceh Tamiang to be better prepared and more self-reliant in facing future flash-flood risks.